1992
DOI: 10.2116/analsci.8.737
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Isotachophoresis

Abstract: A computer simulation of isotachophoresis is described for the purpose of determining physico-chemical constants and separation optimization. On the basis of the mobilities, dissociation constants and stability constants of the separands, the effective mobilities and the isotachopherogram in the steady state condition can be exactly simulated at a given electrolyte condition. When some of the necessary constants are unknown, they can be evaluated by means of a leastsquares method on the basis of the observed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Computers can be used to solve the mathematical model for a variety of electrokinetic separation techniques and experimental system conditions. Hirokawa et al developed a model that uses an iterative scheme to vary the pH of each analyte zone in ITP and determine its concentration and effective mobility [27,33,34]. However, this model is limited to cases where the ITP has reached a steady state.…”
Section: Computer Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computers can be used to solve the mathematical model for a variety of electrokinetic separation techniques and experimental system conditions. Hirokawa et al developed a model that uses an iterative scheme to vary the pH of each analyte zone in ITP and determine its concentration and effective mobility [27,33,34]. However, this model is limited to cases where the ITP has reached a steady state.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…Hirokawa et al. developed a model that uses an iterative scheme to vary the pH of each analyte zone in ITP and determine its concentration and effective mobility []. However, this model is limited to cases where the ITP has reached a steady state.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation in the EPD process allows us to better understand the electromigration process and determine the optimal deposition conditions without conducting experiments. Many works have explored the simulation of EPD process thus far. These studies have contributed to the understanding of the processes of zone electrophoresis, moving boundary electrophoresis, , isotachophoresis, isoelectric focusing, and isoelectric trapping . However, no specific studies have clearly shown the effect of the electric field on the thin film structure formed through cathodic electrophoretic deposition of f-MWCNTs.…”
Section: Introductionmentioning
confidence: 99%